Evaluation of Nutritional Composition of The Dried Seaweed Ulva lactuca from Pameungpeuk Waters, Indonesia - Abdullah Rasyid (Tropical Life Sciences Research, 2017)
The nutritional composition of the dried seaweed Ulva lactuca from Pameungpeuk waters, including proximate, vitamins, minerals, dietary fibre and heavy metal has been carried out. The objective of this present study is to know the nutritional composition of the dried seaweed U. lactuca for utilization in human nutrition in the future. Results show that carbohydrate was the major component in the proximate analysis of U. lactuca in the present study. The carbohydrate content was 58.1%. Moisture, ash, protein and fat content were 16.9%, 11.2%, 13.6% and 0.19% respectively, while dietary fibre was 28.4%. The vitamin A content was examined in this study less than 0.5 IU/100 mg while vitamin B1 (thiamine) and vitamin B2 (riboflavin) were 4.87 mg/kg and 0.86 mg/kg respectively. The calcium content was 1828 mg/100 g higher than other minerals. The heavy metal content examined in this study were lower than the limit of the quality criteria applied to edible seaweeds sold in Indonesia. Based on the results of this study show that U. lactuca has potential to be developed as an alternative source of a healthy food for human in the future.